Utopia/Wutuobang as a travelling marker of time - Andolfatto, Lorenzo (The historical journal, 2021)
This article argues for the understanding of ‘utopia’ as a cultural marker whose appearance in history is functional to the a posteriori chronologization (or typification) of historical time. I develop this argument via a comparative analysis of utopia between China and Europe. Utopia is a marker of modernity: the coinage of the word wutuobang (‘utopia’) in Chinese around 1895 is analogous and complementary to More's invention of Utopia in 1516, in that both represent attempts at the conceptualizations of displaced imaginaries, encounters with radical forms of otherness - the European ‘discovery’ of the ‘New World’ during the Renaissance on the one hand, and early modern China's own ‘Westphalian’ refashioning on the other. In fact, a steady stream of utopian conjecturing seems to mark the latter: from the Taiping Heavenly Kingdom borne out of the Opium wars, via the utopian tendencies of late Qing fiction in the works of literati such as Li Ruzhen, Biheguan Zhuren, Lu Shi'e, Wu Jianren, Xiaoran Yusheng, and Xu Zhiyan, to the reformer Kang Youwei's monumental treatise Datong shu. Altogether, these sketches of utopia provide an imaginary counterpoint to the co-produced regimes of historicity whose genealogies are being traced in this issue.
Gesehen am 09.09.2021
First published: 01 September 2020